Assessment of Chemical Impact of Invasive Bryozoan Pectinatella magnifica on the Environment: Cytotoxicity and Antimicrobial Activity of P. magnifica Extracts - Kollar, Peter (Molecules, 2016)
Pectinatella magnifica, an invasive bryozoan, might significantly affect ecosystem balance due to its massive occurrence in many areas in Europe and other parts of the world. Biological and chemical analyses are needed to get complete information about the impact of the animal on the environment. In this paper, we aimed to evaluate in vitro cytotoxic effects of five extracts prepared from P. magnifica using LDH assay on THP-1 cell line. Antimicrobial activities of extracts against 22 different bacterial strains were tested by microdilution method. Our study showed that all extracts tested, except aqueous portion, demonstrated LD(50) values below 100 μg/mL, which indicates potential toxicity. The water extract of P. magnifica with LD(50) value of 250 μg/mL also shows potentially harmful effects. Also, an environmental risk resulting from the presence and increasing biomass of potentially toxic benthic cyanobacteria in old colonies should not be underestimated. Toxicity of Pectinatella extracts could be partially caused by presence of Aeromonas species in material, since we found members of these genera as most abundant bacteria associated with P. magnifica. Furthermore, P. magnifica seems to be a promising source of certain antimicrobial agents. Its methanolic extract, hexane, and chloroform fractions possessed selective inhibitory effect on some potential pathogens and food spoiling bacteria in the range of MIC 0.5–10 mg/mL. Future effort should be made to isolate and characterize the content compounds derived from P. magnifica, which could help to identify the substance(s) responsible for the toxic effects of P. magnifica extracts.